General Sudirman's Philosophy Based on Colonialism in the Film Jendral Sudirman Implications for Current Conditions Historical Study - Simamora, Enjelina Pitri; Hutasoit, Trides Mayora; Harahap, Roamawaty (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
One of Indonesia's national heroes is General Sudirman, who was instrumental in liberating Indonesia from Dutch colonial rule. This article lists General Sudirman's contribution in shaping the spirit of nationalism and patriotism during the colonial occupation and how it affects the current state of nationalism and patriotism in Indonesia. In this article, the author examines the activities of the national hero in the resistance against the Dutch colonial forces. Using a comparison of basic methods and historical analysis. This method is done by involving historical stories and documents, meaning that representation is expressed in the relationship between General Sudirman's battle and the colonizers.